Genomic characteristics of predominant SARS-CoV-2 variants in Guizhou province from 2020 to 2023: a whole genome sequencing analysis of respiratory tract specimens - Li ZHUANG; Qian KE; Ju ZHENG; Ping WU; Weijia JIANG (Editorial Office of Chinese Journal of Public Health, 2024)
ObjectiveTo understand the genomic characteristics of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) circulating in Guizhou province from 2020 to 2023, and to elucidate its genetic variation and susceptibility changes caused by mutations in key amino acid sites. MethodsA total of 316 SARS-CoV-2 positive oropharyngeal and nasopharyngeal swabs were collected in Guizhou province from 2020 to 2023. High-throughput sequencing technology was used for viral genome amplification and sequencing. The offline data were analyzed by Nextclade online data analysis platform to determine the virus type and evolutionary branch, and to analyze the variation of key amino acid sites and genetic evolution characteristics. ResultsThe complete genome sequence of 259 SARS-CoV-2 strains was successfully obtained, including 59 evolutionary branches. During the first episode (January - August 2020) of coronavirus disease 2019 (COVID-19), the degree of evolution of the virus was relatively limited, and it was mainly the original SARS-CoV-2 strain (Pango type B.1); the second episode of the COVID-19 epidemic (from September 2020 to December 2021) was dominated by the Delta mutant (three evolutionary branches), which contains 36 - 39 amino acid mutations, including about 8 - 10 amino acid mutations in the spike (S) protein; the third episode of the epidemic (from January 2022 to December 2023) was dominated by the Omicron mutant (56 evolutionary branches), which contains about 47 - 66 amino acid mutations, including about 28 - 42 amino acid mutations in the S protein. The top three predominant SARS-CoV-2 variants from 2020 to 2023 in the province were Omicron XBB recombinant and its sub branches, Omicron BA.5.2 and its sub branches, Omicron BF.7 mutant. ConclusionThe virus mutations in the early stage of SARS-CoV-2 infection in Guizhou province from 2020 to 2023 showed higher binding affinity of angiotensin-converting enzyme 2 (ACE2) and partial immune escape ability, while the mutant viruses in the later stage showed higher immune escape ability, leading to an increasing immune gap in the whole population.